Regulation of the global orthotist/prosthetist workforce, and what we might learn from allied health professions with international-level regulatory support: a narrative review - Leigh Clarke; Louise Puli; Emily Ridgewell; Michael P. Dillon; Sarah Anderson (BMC, 2021)
Abstract Background By 2050, the global demand for orthotic and prosthetic services is expected to double. Unfortunately, the orthotic/prosthetic workforce is not well placed to meet this growing demand. Strengthening the regulation of orthotist/prosthetists will be key to meeting future workforce demands, however little is known about the extent of orthotist/prosthetist regulation nor the mechanisms through which regulation could best be strengthened. Fortunately, a number of allied health professions have international-level regulatory support that may serve as a model to strengthen regulation of the orthotic/prosthetic profession. The aims of this study were to describe the national-level regulation of orthotist/prosthetists globally, and the international-level regulatory support provided to allied health professions. Method Two environmental scans benchmarked the national-level regulation of the orthotist/prosthetist workforce, and the regulatory support provided by international allied health professional bodies using a set of nine core practitioner standards (core standards) including: Minimum Training/Education, Entry-level Competency Standards, Scope of Practice, Code of Conduct and/or Ethics, Course Accreditation, Continuing Professional Development, Language Standard, Recency of Practice, and Return-to-Practice. Each identified country was categorised by income status (i.e. High-, Upper-Middle-, Lower-Middle-, and Low-Income countries). Results Some degree of regulation of the orthotist/prosthetist workforce was identified in 30 (15%) of the world's 197 countries. All core standards were present in 6 of these countries. Countries of higher economic status had more core standards in place than countries of lower economic status. International-level professional bodies were identified for 14 of 20 allied health professions. International bodies for the physical therapy (8 core standards) and occupational therapy (5 core standards) professions provided regulatory support to help national associations meet most of the core standards. Conclusion Given the small proportion of countries that have national practitioner regulatory standards in place, most orthotist/prosthetists are working under little-to-no regulation. This presents an opportunity to develop rigorous national-level regulation that can support workforce growth to meet future workforce demands. Given the financial and expertise barriers that hinder the development of a more regulated orthotist/prosthetist workforce, particularly for Low- and Lower-Middle-Income countries, we recommend the establishment of an international professional body with the express purpose to support national-level regulation of orthotist/prosthetists, and thereby build the regulatory capacity of national orthotic/prosthetic associations.